Rancang Bangun Sistem Automatic Semi Returnless Berbasis Arduino Uno pada Engine Caterpillar C27 Studi Kasus PT. Sapta Indra Sejati - Widi Achmad Sukisno, Sulis; Suparno, Joko; Ardiansyah Halim, Dimas (Accurate: Journal of Mechanical Engineering and Science, 2022)
Pump units with a Caterpillar C27 engine with an EUI (Electronic Unit Injector) fuel system that often has low power due to filter clogging at PT. Sapta Indra Sejati. Filter cloggingoccurs due to due to the thickened biofuel content and creates a crust. If the machine has a problem, the mining process can be disrupted because the coal loading area is flooded. This study aims to create an additional system in the form of a automatic semi-returnless where the fuel return line is changed automatically into the filter because the fuel return is clean. The movement of the return control valve is regulated by a microcontroller which is programmed according to specifications and needs. The microcontroller used is Arduino Unowith pressure and temperature sensors. Arduino Uno is programmed when the engine will experience low power with a fuel pressure of 400 kPa then the return path is changed to semi returnless. With a change in the semi returnless path, the pressure becomes stable at 380 kPa and the engine RPM is stable with power that is still maintained. The advantages of semi-returnless system are that filter replacement costs can be reduced and production time is not interrupted.